Agricultural drought risk assessments: a comprehensive review of indicators, algorithms, and validation for informed adaptations - Tien Le; Chayn Sun; Suelynn Choy; Yuriy Kuleshov; Trinh Duc Tran (Geomatics, Natural Hazards & Risk)
This literature review discusses specific challenges associated with drought risk assessments (DRA) within agricultural systems, particularly concerning the justification for indicator selection, aggregation methods, and DRA-informed adaptation strategies. Employing a multifaceted approach combining quantitative and qualitative methods, we systematically reviewed existing DRA literature. The PRISMA methodology and bibliometric analysis were employed to quantitatively reveal trends, key contributors, and publication patterns in DRA research, offering insights into the research evolution in the field. Simultaneously, the qualitative aspect of this review involved an examination of selected papers to identify critical gaps. Our analysis reveals that 67% of the studies lack validation for their research methodology, underscoring the need for rigorous validation of DRA results to enhance research credibility among decision-makers. Additionally, a significant 88% of the reviewed papers primarily focus on risk identification, with less emphasis on adaptation strategies derived from DRA results. Therefore, we emphasize the imperative of bridging the gap between DRA research and practical applications, advocating for linking drought risk findings to adaptation strategies. This targeted approach allows for the identification of sector-specific indicators, methodologies, and adaptation strategies to address the unique vulnerabilities of agriculture, ultimately enhancing the effectiveness of drought risk management and adaptation efforts in agricultural contexts.